USIA MENOPAUSE DAN KEJADIAN OSTEOPOROSIS PADA LANSIA - R, Sri Zulfi; Zein, Asmar Yetti; Sujiyatini, Sujiyatini (Poltekkes Kemenkes Yogyakarta, 2014)
Menopouse age in Indonesian women which faster can effect to osteoporosis incident. Beside that raising of live expectation have more effect to get illness at late age, such as osteoporosis. The raising of osteoporosis incident at late age would be health problem which needed to notice and got serious support. Based on data from Banguntapan I Local Government clinic Bantul had 3020) late age and women at late age in range above 60 years old are 600 people (20%). Those 20% are women with osteoporosis risk. To identify correlation of menopouse age with osteoporosis incident. This study is an analutic observational with cross-sectional design. This study held in Banguntapan I Local Government clinic Bantul area at Januari 25, 2013. Subjek of study are women at late age and had incluci and exclusi criteria. Amount of sample are 156 participant. Instrument of study is roundup data form. Analysis used kendall-tau test by p < 0,05 and conffident interval 95% than used coefficient correlation test. Normal meopouse age at late age are 44% whereas late menopouse age at late age are 56%. Osteoporosis incident at late age who at normal menopouse age are 56% whereas at late menopouse age are 44%. Women at late age who come to menopouse stage are risk to have osteoporosis by p-value 0,000. There is a significant correlation statisticly of menopouse age with osteoporosis.